Kejadian Ekstravasasi Obat Kemoterapi pada Pasien Kanker - Manik, Marisa Junianti (Jurusan Keperawatan FIKES UNSOED, 2016)
Chemotherapy is a cancer management with drugs. The complication that can be occurred is extravasation. The objective of this study was to analyze factors such as vein conditions, type of medications/chemotherapeutic agents, volume of chemotherapeutic agents, and their correlation with chemotherapy drugs extravasation incidences. This study used cross-sectional observational analytic design, with purposive sampling. The sample of this study was 70 cancer patients undergoing chemotherapy in hospitals. Inclusive criteria were patients with ages 18-65 in their first to fifth cycle of chemotherapy. The observation form was used as research instrument. The study showed that there were no correlation between vein conditions, type of medications/chemotherapeutic agents, and volume of chemotherapeutic agents with extravasation. Most veins were still in good condition while undergoing chemotherapy. The length of time for administering chemotherapy were mostly